Understanding the societal impact of research through productive interactions and realist theory-based evaluation: Select cases of agricultural research in South Africa - Esterhuyse, Harrie Willie (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.